Neurosyphilis and classical music: the great composers and “The Great Imitator” - Matheus Kahakura Franco Pedro (Arquivos de Neuro-Psiquiatria)
ABSTRACT Throughout history, neurosyphilis has victimized many people, including classical composers, with a wide range of clinical presentations. Methods: Six articles with descriptions of composers with possible neurosyphilis were reviewed. Results: Neurosyphilis is a possible diagnosis for composers like Beethoven, whose progressive hearing loss influenced his career, culminating in complete deafness. In his autopsy, cochlear nerve atrophy and cochlear inflammation were described. Donizetti developed behavioral changes, as well as headaches, general paresis and seizures. Both Schumann and Wolf suffered from personality changes, persecutory delusions and general paresis. Joplin and Delius also had symptoms attributed to syphilis. Autopsy findings confirmed the diagnosis of Smetana, who developed dementia, deafness and auditory hallucinations with rapid progression. His tinnitus was musically represented in his first String Quartet. Conclusion: Neurosyphilis victimized several notorious composers. It can be argued that neurosyphilis was a major source of inspiration as well, being responsible for the genesis of musical masterpieces.